Pharmacological Therapy of Osteoporosis: A Systematic Current Review of Literature - Pavone, Vito; Testa, Gianluca; Giardina, Serena M. C.; Vescio, Andrea; Restivo, Domenico A.; Sessa, Giuseppe (Frontiers in Pharmacology, 2017)
Osteoporosis is the most common bone disease affecting millions of people worldwide, particularly in elderly or in post-menopausal women. The pathogenesis is useful to understand the possible mechanism of action of anti-osteoporotic drugs. Early diagnosis, possible with several laboratory and instrumental tests, allows a major accuracy in the choice of anti-osteoporosis drugs. Treatment of osteoporosis is strictly related to severity of pathology and consists on prevention of fragility fractures with a correct lifestyle and adequate nutritional supplements, and use of pharmacological therapy, started in patients with osteopenia and history of fragility fracture of the hip or spine. The purpose of this review is to focus on main current pharmacological products to treat osteoporotic patients.